2009
DOI: 10.3390/molecules14020894
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 1α,25-Dihydroxyvitamin D Analogues Featuring a S2-symmetric CD-ring Core

Abstract: Three analogues of 1α,25-dihydroxyvitamin D3 (calcitriol), featuring a trans-fused decalin C,D-core with local S2-symmetry, and possessing identical side-chain and seco-B,A-ring structures, have been synthesized starting from readily available (4aR,8aS)-octahydronaphthalene-1,5-dione (7). The very short sequences involve the simultaneous introduction of the side-chain and seco-B,A-ring fragments via Suzuki and Sonogashira coupling reactions. The analogues are devoid of relevant biological activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The 1β-analogues (31,33) showed significant antiproliferative activity in murine keratinocytes and malignant melanoma cells, and this was equally potent to or even more potent than 1α,25(OH) 2 D 3 (2). On the other hand, 1α-analogues (30,32) were much less potent than their 1β-counterparts (31,33). In addition, 31 and 33 showed no calcemic activity in vivo.…”
Section: -Ene-vitamin D 3 Analoguesmentioning
confidence: 98%
See 3 more Smart Citations
“…The 1β-analogues (31,33) showed significant antiproliferative activity in murine keratinocytes and malignant melanoma cells, and this was equally potent to or even more potent than 1α,25(OH) 2 D 3 (2). On the other hand, 1α-analogues (30,32) were much less potent than their 1β-counterparts (31,33). In addition, 31 and 33 showed no calcemic activity in vivo.…”
Section: -Ene-vitamin D 3 Analoguesmentioning
confidence: 98%
“…The same authors subsequently reported the 1-hydroxymethyl-24,24-difluoro-16-ene analogues (30)(31)(32)(33) in 1998 [19]. The 16-ene-homoallylic alcohol (35) provided by an ene reaction of olefin (34) was first converted to tosylate via tosylation of the primary hydroxy group and triethylsilylation of the secondary hydroxy group.…”
Section: -Ene-vitamin D 3 Analoguesmentioning
confidence: 99%
See 2 more Smart Citations
“…This type of analog featuring structural symmetry could bind in two different and opposite directions within the LBD. Figure 76.5 presents pseudo-symmetrical analogs with a trans-fused decalin CD-core with local S 2 -symmetry possessing identical seco-B,A-ring structures (GM 7, GM 8, GM 15, and GM 14) [27]. The side chain section contains structural modifications similar to the so-called arocalciferols [28] and 16-ene analogs [29].…”
Section: Decalin Analogsmentioning
confidence: 99%